Escola: lugar político da diversidade sexual e de gênero - Duarte, Maria Leuca Teixeira (2015)
This work aims to understand how the public school system has become a failing institution with regards to sexual and gender diversity. I start from the principle that the school system performs a social sorting operation, leaving out of its halls almost all people who don‘t fit into the established heteronormative social order. First, I explore the experiences of primary school (Educação do Ensino Fundamental) professionals from the public network (Rede Pública Municipal) of the city of Natal-RN. I consider their narratives a result of daily practices which denounce the rules that govern and produce them in a broader context. Then I aim to establish a dialogue with the students who are victims of name-calling, teasing and abuse for not aligning with the ―normal‖ gender standards. At this stage of the research, I conducted fieldwork at the State Secondary School of Rio Grande do Norte (Escola Estadual de Ensino Médio). This investigation is guided by the following questions: What challenges need to be addressed in order to recognize the students who have been excluded from the school environment on account of sexual and/or gender differences; additionally, how can their classroom attendance and positive learning experience be ensured? To what degree is the school community concerned with building education practices which value and acknowledge sexual and gender diversity? The research goals were: to analyze how the school and its professionals deal with sexual and gender diversity, investigating which pedagogical practices silence, freeze and obstruct the diversity of student identities; examine how the school and its subjects work toward building new pathways for learning, for coexistence, and for facing the challenges of ―new‖ social demands such as homoaffection; observe the spaces that are cracked open by the presence and the voices of students who demand recognition of their existence.